Validation of QTLs associated with corn borer resistance and grain yield: implications in maize breeding - López-Malvar, Ana; Reséndiz-Ramirez, Zoila; Butrón, Ana; Jiménez-Galindo, Jose Cruz; Revilla, Pedro; Malvar, Rosa Ana (Frontiers in Plant Science, 2024)
Validations of previously detected QTL to assess their reliability are crucial before implementing breeding programs. The objective of this study was to determine the reliability and practical usefulness of previously reported QTL for resistance to stem tunneling by the Mediterranean stem borer and yield in a Multiparent Advanced Generation Inter-Cross (MAGIC) population of maize. RIL situated at the extremes of resistance and yield distributions within the whole MAGIC, were evaluated per se and crossed to a tester using lattice designs. A significant SNP was considered validated if: 1) the same SNP was associated with the trait with a p-value < 0.02, or 2) within a ± 2Mbp interval, a SNP associated with the trait exhibited a p-value < 0.02 and demonstrated linkage disequilibrium (r2 > 0.2) with the SNPs previously reported. The procedure used allowed to jointly validate several QTL and to ascertain their possible contribution to hybrid improvement. These findings offer insights into the reliability of QTL and genomic predictions, both derived from assessments conducted on the entire MAGIC population. Genomic predictions for tunnel length based on inbred line evaluations could be useful to develop resistant hybrids; meanwhile for yield could only be valid in a homozygous background.